American traitor [compact disc, unabridged] - Taylor, Brad, 1965- (A Pike Logan novel, 2021)
A soldier who was trained to fight and win, Pike Logan is now pitted against an invisible enemy that he can't actually attack, as he learns of a scheme that could launch a full-on war between China and Taiwan.